Understanding the evidence gaps: Diets and fruit and vegetable intake across five diverse low- and middle-income countries - Tharaney, Manisha; Hess, Sonja Y.; Bliznashka, Lilia; Amunga, Dorcas A.; Azupogo, Fusta; Koyratty, Nadia; Smith, Taryn J.; Angeles-Agdeppa, Imelda; Goyena, Eva A.; Grant, Frederick; Kinabo, Joyce; Mitchodigni, Irene Medeme; et al. (Wiley, 2026)
Poor dietary quality, particularly inadequate fruit and vegetable (F&V) intake, remains a significant public health challenge globally. This article synthesizes findings from scoping reviews examining diet and F&V intake, and interventions to increase F&V consumption among population groups in five countries: Benin, Fiji, the Philippines, Sri Lanka and Tanzania. Our analysis confirms previous findings of inadequate F&V intake across all five countries, with most adults consuming well below the WHO recommendations of 400 g per day. Across the five countries, the identified scientific evidence is limited due to heterogeneous dietary assessment methods, limited coverage of population groups in national surveys and smaller studies, and limited data from rigorous evaluations of interventions aiming to increase F&V intake. Although all five countries have developed food-based dietary guidelines promoting F&V intake, research on their implementation and effectiveness remains limited. To build evidence for effective programmes and policies to improve both quantity and diversity of F&V intake, we identify three priority areas for future research: standardizing dietary assessment methods for use in surveys and evaluations, understanding context-specific drivers and determinants of F&V intake and strengthening intervention research in low-resource settings.